Tracking X-ray outflows with optical/infrared footprint lines. Issue 1 (27th January 2022) - Trindade Falcão, Anna; Kraemer, S B; Crenshaw, D M; Melendez, M; Revalski, M; Fischer, T C; Schmitt, H R; Turner, T J
ABSTRACT: We use cloudy photoionization models to predict the flux profiles for optical/infrared (IR) emission lines that trace the footprint of X-ray gas, such as [Fe x ] 6375 Å and [Si x ] 1.43 μm . These are subset of coronal lines, from ions with ionization potential greater than or equal to that of O vii, i.e. 138 eV. The footprint lines are formed in gas over the same range in ionization state as the H- and He-like of O and Ne ions, which are also the source of X-ray emission lines. The footprint lines can be detected with optical and IR telescopes, such as the Hubble Space Telescope /STIS and James Webb Space Telescope /NIRSpec, and can potentially be used to measure the kinematics of the extended X-ray emission gas. As a test case, we use the footprints to quantify the properties of the X-ray outflow in the type 1 Seyfert galaxy NGC 4151. To confirm the accuracy of our method, we compare our model predictions to the measured flux from archival STIS spectra and previous ground-based studies, and the results are in good agreement. We also use our X-ray footprint method to predict the mass profile for the X-ray emission-line gas in NGC 4151 and derive a total spatially integrated X-ray mass of 7.8(± 2.1) × 10^5 M_, in comparison to 5.4(± 1.1) × 10^5 M_ measured from a Chandra X-ray analysis. Our results indicate that high-ionization footprint emission lines in the optical and near-IR can be used to accurately trace the kinematics and physical conditions of active galactic nucleus-ionized, X-ray emission-line gas.